KOLABORASI PEMBELAJARAN SAINS IPA DI MADRASAH IBTIDAIYAH DENGAN MASYARAKAT KAMPUNG NAGA UNTUK MENGEMBANGKAN PROFIL PELAJAR PANCASILA - Yayan Carlian; Idad Suhada; Nano Nurdiansyah (Al-Aulad: Journal of Islamic Primary Education, 2025)
This study aims to explore and integrate the local wisdom of Kampung Naga as a learning resource in Madrasah to develop the Pancasila Student Profile. The research employed a mixed-method approach with an explanatory design, combining qualitative and quantitative data. Participants included the indigenous community of Kampung Naga, teachers, and students of MI Arrohmah Dadaha Tasikmalaya. Data were collected through observation, interviews, and documentation, then analyzed thematically for qualitative data and by using the N-gain test for quantitative data. Data validity was ensured through source and method triangulation. The findings reveal that various forms of local wisdom, such as environmental management, traditional agricultural systems, water conservation, and sustainable living practices, can serve as contextual science learning resources for students. The collaboration between Madrasah Ibtidaiyah and the Kampung Naga community encourages meaningful and applicable learning experiences. This collaborative learning model has been proven to enhance several dimensions of the Pancasila Student Profile, including being faithful and pious to God Almighty, independent, cooperative, critical-thinking, and creative.